Quantitative Research Philosophy in Research Methodology - Mahardini, Dzakia Fifi; Kasenda, Ikas; Afgani, Muhammad Win; Isnaini, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The research carried out aims to find out uncertain truths based on findings from the core of the problem. A complete explanation of research philosophy can be explained with the possibility of several paradigms and from a physiological perspective. The purpose of this paper is to explain the philosophy of quantitative research, explain the development of quantitative research philosophy and the characteristics of quantitative research. The method used in the research is a library research method. In this research, a critical study was also carried out of the thoughts of figures sourced from book literature and journals related to the material presented in the form of philosophy from quantitative research. Quantitative research is defined as research that is based on the philosophy of positivism, generally used to research certain populations or samples, sampling techniques are generally carried out randomly, data collection uses research instruments, data analysis is quantitative/statistical with the aim of testing predetermined hypotheses. The philosophy of positivism holds that reliable knowledge is factual knowledge obtained through observation and measurement.